2011
DOI: 10.1007/s00384-011-1386-2
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal quality of life after laparoscopic-assisted sigmoidectomy for diverticular disease

Abstract: The results in this study population show that in a majority of patients who underwent elective laparoscopic-assisted sigmoidectomy for recurrent diverticulitis gastrointestinal quality of life improved with the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…Both studies found a substantial improvement of gastrointestinal symptoms on the Gastro-Intestinal Quality of Life Index (GIQLI) after elective resection for diverticular disease. Pasternak et al [14] reported an overall success rate of 96% in gastrointestinal symptoms, which corresponds well with the success rates found in this study. Notably, a major difference between the abovementioned studies and this study is the instrument for measuring QoL and symptoms.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Both studies found a substantial improvement of gastrointestinal symptoms on the Gastro-Intestinal Quality of Life Index (GIQLI) after elective resection for diverticular disease. Pasternak et al [14] reported an overall success rate of 96% in gastrointestinal symptoms, which corresponds well with the success rates found in this study. Notably, a major difference between the abovementioned studies and this study is the instrument for measuring QoL and symptoms.…”
Section: Discussionsupporting
confidence: 81%
“…Comparable studies with similar study populations were performed by Forgione et al [2 ]in 2009 and more recently by Pasternak et al [14]. Both studies found a substantial improvement of gastrointestinal symptoms on the Gastro-Intestinal Quality of Life Index (GIQLI) after elective resection for diverticular disease.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, surgery for diverticulitis does not seem to fully protect against the risk of recurrence since the incidence of recurrent attacks is between 5.8 and 15 % [111,115,127], and risk of further surgery is up to 3 % [112,115,128,129].…”
Section: Elective Surgery For Diverticular Diseasementioning
confidence: 99%
“…Consequently, current guidelines are not uniform in their suggestions [10,11,12,13,14,15]. In 2000, the standard task force of the American Society of Colon and Rectal surgeons recommended that a sigmoidectomy be performed after a second episode of diverticulitis [10].…”
Section: Introductionmentioning
confidence: 99%
“…The Dutch guidelines advise that patient-bound factors should be taken into account when making a decision to perform sigmoidectomy in patients with ongoing complaints and recurrent disease, rather than the number of episodes alone [11]. Improvement of quality of life (QoL) and discomfort caused by abdominal symptoms may very well outweigh the procedure-related risks and, therefore, form the most compelling reason for offering elective resection [13]. Many surgeons are reluctant to perform elective resections due to the risk of procedure-related complications [2].…”
Section: Introductionmentioning
confidence: 99%